Pleasure-suffering duality in stricto sensu graduate programs in nursing: between bridges and walls - Danielle de Araújo Moreira; Hanna Beatriz Bacelar Tibães; Maria José Menezes Brito
ABSTRACT Objectives: to understand the pleasure-suffering duality experienced by students in stricto sensu Graduate Program in Nursing. Methods: qualitative, integrated single-case study based on the Psychodynamics of Work. The setting was the stricto sensu Graduate Program in Nursing in Brazil. Two Graduate Programs were chosen. Data collection took place between May 2017 and April 2018, with 23 students, through interviews guided by semi-structured script and Documentary Analysis. Content Analysis was carried out. Results: two analysis units emerged: Situations generating pleasure: bridges built by the Graduate Program and Situations generating suffering: walls of the Graduate Program. They were discussed in two dimensions - organizational and socio-professional relations. Final considerations: the results can contribute to the planning of actions capable of potentiating the creation of "bridges" that lead to reach of pleasure in the Graduate Program. It impels the confrontation of suffering-generating situations for the student.